2014
DOI: 10.1371/journal.pone.0100231
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Determinants of Socioeconomic Inequality in Health Service Utilization among Patients with Chronic Non-Communicable Diseases in China

Abstract: BackgroundPeople with chronic non-communicable diseases (NCD) are particularly vulnerable to socioeconomic inequality due to their long-term expensive health needs. This study aimed to assess socioeconomic-related inequality in health service utilization among NCD patients in China and to analyze factors associated with this disparity.MethodsData were taken from the 2008 Chinese National Health Survey, in which a multiple stage stratified random sampling method was employed to survey 56,456 households. We anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
81
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(94 citation statements)
references
References 43 publications
9
81
3
1
Order By: Relevance
“…Most previous studies in China have focused on socio‐economic inequality in healthcare utilisation among the general population or among people with chronic diseases . Some studies have also examined the degree of CHE or health impoverishment at the sub‐national level or in rural areas in China .…”
Section: Introductionmentioning
confidence: 99%
“…Most previous studies in China have focused on socio‐economic inequality in healthcare utilisation among the general population or among people with chronic diseases . Some studies have also examined the degree of CHE or health impoverishment at the sub‐national level or in rural areas in China .…”
Section: Introductionmentioning
confidence: 99%
“…Poor and disadvantaged sections of the population face more financial risks and need better financial mechanisms to avail healthcare services [21, 22]. Literature also indicates differentials in healthcare spending among various regions as well as segments of population [23, 24]. …”
Section: Introductionmentioning
confidence: 99%
“…An effective job in EMS could save resources for subsequent treatment and reduce both the morbidity and mortality rates [12]. Moreover, studies have shown that patients do not use EMS due mainly to a lack of medical expenses, knowledge, and technical resources [13]. In fact, the distance and transportation costs of EMS can be declined by encouraging the use of ambulance.…”
Section: Introductionmentioning
confidence: 99%